2010
DOI: 10.1177/147323001003800118
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Consumption and Recovery Profiles According to Anaesthetic Circuit Mode using a New Multifunctional Closed-Circuit Anaesthesia System during Desflurane Anaesthesia: A Clinical Study

Abstract: This clinical study compared induction time, consumed anaesthetic dose, and haemodynamic and recovery profiles when using a new type of multifunctional anaesthesia machine (Zeus) in semi-closed or closed circuit modes. Sixty female patients undergoing gynaecological surgery were randomly assigned to three groups and received desflurane anaesthesia through a semi-closed circuit (SCC) at fresh gas flow rates of 4 l/min (SCC 4 l/min) or 2 l/min (SCC 2 l/min), or through a closed circuit (CC). Anaesthesia was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Kern et al [7] reported that, in toddlers and newborns, the time to target concentration shortens at high FGF rates, at small internal volumes of the AM, and at high minute ventilations. In the present study, the Primus ® [7, 12], Perseus ® [13], and Zeus ® (Zeus ® -F and Zeus ® -A) [5, 6, 14, 15] differed in the following ways: (1) type of ventilator, (2) internal volume, (3) proximity of the fresh gas inlet to the patient, (4) presence of the decoupling system, (5) type of vaporizer, and (6) involvement of TCA (Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kern et al [7] reported that, in toddlers and newborns, the time to target concentration shortens at high FGF rates, at small internal volumes of the AM, and at high minute ventilations. In the present study, the Primus ® [7, 12], Perseus ® [13], and Zeus ® (Zeus ® -F and Zeus ® -A) [5, 6, 14, 15] differed in the following ways: (1) type of ventilator, (2) internal volume, (3) proximity of the fresh gas inlet to the patient, (4) presence of the decoupling system, (5) type of vaporizer, and (6) involvement of TCA (Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…In the Primus ® and Zeus ® -F, the times to target sevoflurane concentration were longer than needed with Perseus ® , because (1) the fresh gas inlets were not close to the patient in either Primus ® or Zeus ® , (2) Primus ® has a large internal volume, (3) Primus ® has a decoupling system, and (4) Zeus ® has two modes of vaporization with the direct injection of volatile anesthetics (DIVA; Table 1) [5, 6, 12–14, 17]. The Primus ® and Perseus ® use a semi-closed circuit system and a bypass vaporizer (out-of-circle vaporization), whereas Zeus ® is the multifunctional system that can operate a semi-closed circuit system (out-of-circle vaporization) or closed-circuit system (in-circle vaporization) using the DIVA vaporizer.…”
Section: Discussionmentioning
confidence: 99%
“…Lortat Jacob et al observed a 65% reduction in the consumption of desflurane and a 50% reduction for fresh gas with the Zeus® machine from Drager [3]. Park et al demonstrated a 5-fold reduction in halogenated agent consumption with the Zeus® TCIA system as compared to its standard use with manual adjustment and a 2 l.min-1 fresh gas flow [6]. Others observed smaller reductions [7].…”
Section: Introductionmentioning
confidence: 93%
“…Nevertheless, studies evaluating the Dräger Zeus Ò Infinity Ò Empowered (IE) ventilator -the only closed-circuit ventilator available in North Americahave generated mixed results. [1][2][3][4][5] Most studies evaluating the closed-circuit machine and semi-closed-circuit machines have compared the automated mode of the Zeus IE with the traditional semi-closed-circuit run by the anesthesiologist under optimal conditions. Our goal was to investigate whether the closed-circuit ventilator offers a reduction in the consumption of volatile agent without requiring anesthesiologists to change their practice habits.…”
Section: To the Editormentioning
confidence: 99%